2011
DOI: 10.1038/gt.2011.133
|View full text |Cite
|
Sign up to set email alerts
|

LOX-1 abrogation reduces cardiac hypertrophy and collagen accumulation following chronic ischemia in the mouse

Abstract: We hypothesized that lectin-like oxidized LDL receptor-1 (LOX-1) deletion may inhibit oxidative stress signals, reduce collagen accumulation and attenuate cardiac remodeling after chronic ischemia. Activation of LOX-1 plays a significant role in the development of inflammation, apoptosis and collagen signals during acute ischemia. Wild-type and LOX-1 knockout (KO) mice were subjected to occlusion of left coronary artery for 3 weeks. Markers of cardiac hypertrophy, fibrosis-related signals (collagen IV, collage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 35 publications
4
35
1
2
Order By: Relevance
“…Besides chronic ischemia, LOX1 may also be detrimental for cardiac damage that occurs in ischemia-reperfusion. Specifi cally, LOX-1 increased in rat cardiomyocytes following ischemia-reperfusion, while administration of anti-LOX-1 antibody reduced myocardial infarction size [ 120 ] and LOX-1 genetic deletion reduced ischemia-driven collagen accumulation [ 121 ]. Therefore, LOX-1 appears to be involved in ischemic heart failure as it activates stress signaling kinases, such as JNK and ERK [ 112 ].…”
Section: Ischemiamentioning
confidence: 97%
See 1 more Smart Citation
“…Besides chronic ischemia, LOX1 may also be detrimental for cardiac damage that occurs in ischemia-reperfusion. Specifi cally, LOX-1 increased in rat cardiomyocytes following ischemia-reperfusion, while administration of anti-LOX-1 antibody reduced myocardial infarction size [ 120 ] and LOX-1 genetic deletion reduced ischemia-driven collagen accumulation [ 121 ]. Therefore, LOX-1 appears to be involved in ischemic heart failure as it activates stress signaling kinases, such as JNK and ERK [ 112 ].…”
Section: Ischemiamentioning
confidence: 97%
“…Abrogation of LOX-1 in an animal model of chronic ischemia reduced infarct size, improved cardiac hemodynamics, prevented cardiac remodeling and fi brosis and improved survival [ 121 ]. Besides chronic ischemia, LOX1 may also be detrimental for cardiac damage that occurs in ischemia-reperfusion.…”
Section: Ischemiamentioning
confidence: 98%
“…The homozygous LOX-1 KO mice were developed and backcrossed eight times with C57BL/6 strain to replace the genetic background [8,11]. This investigation conforms to the Guide for the Care and Use of Laboratory Animals published by the US National Institutes of Health (NIH Publication No.…”
Section: Animal Protocolmentioning
confidence: 99%
“…In recent studies, LOX-1 deletion was shown to limit cardiac hypertrophy and the remodeling process in mice subjected to sustained hypertension or myocardial ischemia. [8][9][10] Part of the decrease in cardiac remodeling with LOX-1 deletion seems to be related to reduction in fibrosis in the heart. 8 In view of markedly reduced collagen deposition and fibrosis in the LOX-1 knockout (KO) mice hearts, we posited that LOX-1 may modulate fibroblast growth, a key factor for cardiac fibrosis.…”
mentioning
confidence: 99%
“…Кроме того, есть данные, что мЛПНП сами по себе могут вступать во взаимодей-ствие и активировать СРБ [19]. Важно отметить, что, кроме активации системы комплемента, LOX-1 [20] и СРБ [21] могут сами непосредственно участвовать в фиброзе миокарда. Таким образом, повышение уров-ня мЛПНП запускает многофакторные процессы, которые в конечном итоге могут приводить к фиброзу миокарда.…”
unclassified